DEVELOPMENT OF INSTRUCTIONAL DESIGN ARABIC-INDONESIAN TRANSLATION BASED ON COLLABORATIVE LEARNING - Setiadi, Syamsi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
The ability to translate is one of the language skills that involves two languages both source language and the target language. This skill requires a good mastery of both languages, so it takes a lot of practice and adequate exercise. Learning Arabic-Indonesian translation based on a collaborative learning approach is one way that can be taken to improve the students’ ability in translating. This research was conducted to develop an instructional design model of Arabic-Indonesian translation based on the collaborative learning method. The research method applied was the Research and Development. The data collection techniques were observations, interviews, and questionnaires. The data analysis of qualitative and quantitative approaches was employed. Based on the results obtained that there is a significant increase students' ability in translating Arabic text into the text of Indonesia based on the significance test the average difference using t-test obtained t-test of 11.02 greater than t-table 2.68, which means that there are significant differences between the average value of the pretest and posttest. Based on the research finding, a conclusion can be drawn that field development constitutes the product of the learning model of Arabic-Indonesian translation for Arabic Department students of Jakarta State University.